We saw in Spain (pamphlet) - Dugdale, John ; Wilkinson, Ellen Cicely, 1891-1947 ; Noel-Baker, Philip Noel-Baker, Baron ; Malindine, E. G.; Attlee, Clement, 1883-1967
1937 WE SAW IN SPAIN Our four visitors with the two youngest members of the Regimental Band. Spain Fights for Democracy By the Rt. Hon. C.R. ATTLEE, M.P. These Children are Spain's Future By ELLEN WILKINSON, M.P. Five Days' Diary of Our Visit By JOHN DUGDALE. Spain's Struggle and the World By PHILIP NOEL BAKER, M.P. WITH 13 PHOTOGRAPHS TAKEN FOR THE "DAILY HERALD" by E.G. MALINDINE 2D 292/946/18a/69(i)